Analisis tingkat kepuasan pelayanan loket pemuatan produk pupuk in-bag menggunakan uji tanda & uji wilcoxon (Studi kasus: PT Petrokimia Gresik) - Oktaviya, Ananta; Pulansari, Farida (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT Petrokimia Gresik is a subsidiary of PT Pupuk Indonesia which is engaged in the fertilizer producer sector. This study was conducted to analyze the level of service satisfaction, measure whether there is a significant difference before and after implementation using the normality test, non-parametric statistics (sign test and Wilcoxon test), and correlation test. In the sign test and Wilcoxon test, 0 data with negative differences, 0 data ties, and 100 data positive differences were obtained from a total of 100 data. In the sign test, the Z-score value was -9.900 and in the Wilcoxon test, the Z-score value was -8.815. In the normality test, the significance value is 0.000, and 0.000 where ? 0.05, indicating that H0 is rejected, then the data is not normally distributed, in the sign test, the significance value is 0.000 ? 0.05 which means H0 is rejected, then there is a significant difference between before and after the implementation of Smart Warehouse Self Check-In and Check-Out, in the Wilcoxon test, the significance value is 0.000 ? 0.05 which means H0 is rejected, then there is a significant difference between before and after the implementation of Smart Warehouse Self Check-In and Check-Out, in the correlation test, the significance value is 0.000 ? 0.05, then H0 is rejected and H1 is accepted, meaning there is a correlation between the data before and after the implementation of Smart Warehouse Self Check-In and Check-Out. This research can help solve problems and improve the level of service at the Warehouse and Packing Department counters.